Observation Depth Measure in a Sample in the Voivodeship Classification of the Property Market - Kobylińska, Małgorzata (Olsztyn Economic Journal, 2013)
The problem of classification has long been an object of interest in many fields of knowledge. It allows homogeneous groups of objects to be obtained with respect to a given criterion. The selection of the appropriate distance measure, which is used in the clustering of multivariate objects, has an important effect on the obtained classification results. This paper uses observation depth measure in a sample ofvoivodeship classification, with respect to selected features concerning the property market in 2011. Voivodeships characterized by typical values for all analysed features were distinguished and those which could be considered outliers were so designated because of high or low values for the studied variables.